Effect of Soaking Java barb (Baryoniums gonionotus) Eggs in Jatropha Leaf Solution (Jatropha curcas L.) on Their Hatching and Survival Rate - Rusda, Yusrotul; Prayitno, Slamet Budi; Hastuti, Sri (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
The biggest problem that often found in barb hatcheries are the poor hatching rate of eggs. One of the causes of low hatchability is infestation of fungi such as Saprolegnia sp. Prevention of the infestation of fungi could be done by adding natural ingredients such as plants leaves that contain antifungal, such as Jatropha leaf. Soaking Jatropha leaf solution aims to protect the chorion from being infestated by fungi so that it can minimize hatching failure of eggs. The purpose of this study was to determine the effect of soaking Jatropha (Jatropha curcas L.) leaf solution on the hatching rate and survival rate of Java barb (Barbonymus gonionotus) eggs. The testing eggs which were used on this study were originated from male and female broodstock aged 1-1.5 years. Experimental method was carried out using a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The treatments were Jatropha leaf solution at dosages of A (0 g/l), B (2 g/l), C (4 g/l), and D (6 g/l). The data observed were embryonic development, hatching rate (HR), survival rate (SR), and water quality. The results showed that treatments C and D demonstrated fastest embryonic development and hatching phase achieved at 475 minutes. Furthermore, treatment C showed the best value with HR (84.00±3.16%), SR (85.24±1.00%). It can be concluded that soaking eggs using Jatropha leaf solution at concentration of 4 g/L significantly improved hatching rate and survival rate of Java barb (Barbonymus gonionotus). Keywords: Jatropha, Java barb eggs, hatchability, fungi